METHODS OF DEVELOPING STUDENTS' LOGICAL THINKING IN PRIMARY EDUCATION (SCIENCE TIME JOURNAL, 2024)
Developing students' logical thinking skills is a crucial aspect of primary education as it equips them with essential cognitive abilities for problem-solving, critical thinking, and decision-making. This article explores various strategies and approaches for fostering logical thinking in primary education. It emphasizes the importance of scaffolding, visual representations, cooperative learning, analogical reasoning, error analysis, and integrating logical thinking across subjects. Additionally, it highlights the significance of real-life problem-solving, reflective journals, assessment methods, and the role of technology in logical thinking development. The article also emphasizes the involvement of parents and the community in supporting students' logical thinking skills. By implementing these strategies, educators can create an environment that cultivates students' logical thinking abilities, preparing them for academic success and lifelong learning.